Analisis Keuangan Inklusif Provinsi Sumatera Barat Tahun 2020 - Willing Alih Maha Ratri (Jurnal Pembangunan Nagari, 2021)
Affordable access to financial services is a driving force for the development of the financial industry, which in turn encourages the growth of the real sector. This study aims to measure the affordability of access to financial services through the regency/municipality Index of Financial Inclusion (IFI) in West Sumatra Province in 2020 using the concept developed by Sarma (2012). Three dimensions used to measure IFI are banking penetration, availability of banking services, and use of banking services. Then descriptive analysis was carried out to evaluate the results of the IKI measurement. The results of the IFI measurement show that the average IFI of regency/municipality in West Sumatra is 0.35, including in the medium category, where Solok Municipality has the highest IFI among other the regencies/municipalities, at 0.96, followed by Bukittinggi and Payakumbuh, are 0.82 and 0.58, respectively. In general, the level of financial inclusion in areas with municipality status is higher than in regency, because, in a municipality area, people have easier access to financial services. IFI can be improved by educating the public about banking products, developing branchless banking to remote areas, and providing easily accessible credit.